Aspectos do princípio da facilitação da defesa do consumidor em juízo em lides individuais - Reberte, Cláudia Maria Chamorro (2009)
This study aims to examine some of the main respects the principle of facilitation of consumer protection in court, provided for by article 6, section VIII, the code of consumer protection, within the individual deal. Will address issues pertaining to competition, shifting the burden of proof, the authority of states obligations to do and not do, and the special civil courts, and how these institutions and instruments to give effect to act principle in question. The analysis takes place from the beginning governing the protective system to the consumer in the CDC, taking account of the imbalance inherent in the relationship of consumption, which stems from the situation of vulnerability of the consumer, and the difficulties for him found with regard to access to justice and their situation in judge